Weather Derivatives: A Contemporary Review and Its Application in China - LIU, Xin (2006)
The weather has impact on both human activity and all forms of businesses. A variety of businesses including energy and power, agriculture, retail, insurance, and entertainment are either favorably or adversely by weather. Then a new class of financial derivatives--weather derivatives are evolved to manage the economic impact of weather events on the performance of business activities. To this day, the weather derivative market has developed throughout the world. Various of weather derivative instruments are traded both on the exchanges and on the over-the-counter market. However, the pricing of weather derivatives remains a crucial problem to mathematicians, meteorologists, derivatives traders and risk managers. Further research is needed to find a standardized pricing approach agreed by all.